2001
DOI: 10.1079/bjn2001391
|View full text |Cite
|
Sign up to set email alerts
|

Learning behaviour and cerebral protein kinase C, antioxidant status, lipid composition in senescence-accelerated mouse: influence of a phosphatidylcholine–vitamin B12diet

Abstract: Our objective was to determine whether dietary supplementation with phosphatidylcholine (PC) plus vitamin B 12 could afford beneficial effects on biochemical and biophysical events in the brain of senescence-accelerated mouse (SAM) substrain SAMP8. We measured learning behaviour, hippocampal protein kinase C (PKC) activity, cerebral antioxidant status, phospholipid composition and fatty acid composition in 6-month-old SAMP8 and in agematched controls (SAM substrain SAMR1). In comparison with SAMR1, SAMP8 showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 44 publications
0
21
1
1
Order By: Relevance
“…TG-or PC-enriched diets have been used for their beneficial effects on central nervous system (CNS) functional disorders (24)(25)(26)(27)(28)(29)(30). The aim of this study was to determine whether these diets modified some aspects of the previously observed alterations of brain lipid metabolism in response to CsA treatment (17), and whether these diets might be useful in a preventive approach toward CsA-induced neurological and psychiatric disorders.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…TG-or PC-enriched diets have been used for their beneficial effects on central nervous system (CNS) functional disorders (24)(25)(26)(27)(28)(29)(30). The aim of this study was to determine whether these diets modified some aspects of the previously observed alterations of brain lipid metabolism in response to CsA treatment (17), and whether these diets might be useful in a preventive approach toward CsA-induced neurological and psychiatric disorders.…”
Section: Discussionmentioning
confidence: 97%
“…Such changes have been suggested to be associated with decreases in brain cholesterol and abnormalities of lipid metabolism (20)(21)(22). Vegetable n-6 polyunsaturated soybean lecithin (phosphatidylcholine: PC), rich in n-6 PUFA, seems to be a suitable dietary supplement during immunosuppressive treatment with CsA since it has been shown to reduce hypercholesterolemia (23), as well as to improve memory and possibly Alzheimer's deficits (24)(25)(26)(27). Dietary triacyglycerol (TG) supplements have no positive effect on blood cholesterol in rats, but have also been shown to improve learning (28).…”
mentioning
confidence: 99%
“…In the section bellow, we will consider the main features that are known to occur early in the pathogenesis of AD and which the SAMP8 strain exhibits, such as increased oxidative stress, amyloid-alterations and tau phosphorylation. Although not commented upon here, other features that have been described in AD pathogenesis have been also found in SAMP8 model as: gliosis (Lu et al, 2009), protein alterations in neurons and astrocytes (Diez-Vives et al, 2009), lower hippocampal PKC activity (Hung et al, 2001), and altered protein expression in the olfactory system (Poon et al, 2005c).…”
Section: Strainmentioning
confidence: 99%
“…These models have been particularly useful for exploring memory deficits (155)(156)(157)(158)(159)(160). These mice are particularly good models of mitochondrial dysfunction and free radical damage (161)(162)(163)(164). The SAMP8 mouse appears to produce its memory deficit due to an excess production of amyloid precursor protein (165)(166)(167)(168).…”
Section: Geriatrics In the Rest Of The Worldmentioning
confidence: 99%